Incisional infiltration versus transversus abdominis plane block of liposomal bupivacaine after midline vertical laparotomy for suspected gynecologic malignancy: a pilot study - Moon, Ashley S.; Andikyan, Vaagn; Agarwal, Rakhee; Stroever, Stephanie; Misita, David; Laibangyang, Anya; Doo, David; Chuang, Linus T. (Gynecologic oncology reports, 2023)
•Incisional infiltration and TAP block are available modalities for acute pain control after gynecologic laparotomy.•Incisional infiltration and TAP block with liposomal bupivacaine have clinically similar postoperative opioid requirement.•Incisional infiltration may be a reasonable alternative in selective situations when TAP block is not readily available. To evaluate whether incisional infiltration of liposomal bupivacaine would decrease opioid requirement and pain scores after midline vertical laparotomy for suspected or known gynecologic malignancy compared with transversus abdominis plane (TAP) block with liposomal bupivacaine. A prospective, single blind randomized controlled trial compared incisional infiltration of liposomal bupivacaine plus 0.5% bupivacaine versus TAP block with liposomal bupivacaine plus 0.5% bupivacaine. In the incisional infiltration group, patients received 266 mg free base liposomal bupivacaine with 150 mg bupivacaine hydrochloride. In the TAP block group, 266 mg free base bupivacaine with 150 mg bupivacaine hydrochloride was administered bilaterally. The primary outcome was total opioid use during the first 48-hour postoperative period. Secondary outcomes included pain scores at rest and with exertion at 2, 6, 12, 24 and 48 h after surgery. Forty three patients were evaluated. After interim analysis, a three-fold higher sample size than originally calculated was required to detect a statistically significant difference. There was no clinical difference between the two arms in mean opioid requirement (morphine milligram equivalents) for the first 48 h after surgery (59.9 vs. 80.8, p = 0.13). There were no differences in pain scores at rest or with exertion between the two groups at pre-specified time intervals. In this pilot study, incisional infiltration of liposomal bupivacaine and TAP block with liposomal bupivacaine demonstrated clinically similar opioid requirement after gynecologic laparotomy for suspected or known gynecologic cancer. Given the underpowered study, these findings cannot support the superiority of either modality after open gynecologic surgery.